Secondary Metabolite Compounds and Secretory Structures of Medicinal Plants in the Piperaceae Family - Darius Rupa; Amran Suparman; Zulfadli Zulfadli (Department of Biology Education, Universitas Borneo Tarakan, 2025)
Species in the Piperaceae family have various benefits and can be used as medicines to treat different kinds of diseases. The metabolite secondary compounds in medicinal plants forms the basis of their medicinal properties, which have been utilized by various ethnics in Indonesia, such as the Dayak Kenyah tribe. This tribe uses plants from the Piperaceae family as traditional medicine. The use of these plants as medicine makes it necessary to analyze the secondary metabolite compounds and the location of their accumulation within the secretory structures using histochemical methods. Plant identification was carried out through direct interviews with local informants and verification at the Herbarium, Indonesian Institute of Sciences. Based on the research results, the plant organs used were mainly leaves, which are generally used as remedies for fever. The secretory structures found include idioblast cells and glandular trichomes, which commonly contain alkaloid and terpenoid compounds. The results of this study strengthen the evidence for the medicinal potential of the four Piperaceae species: Piper betle, Piper porphyrophyllum, Piper officinarum, and Piper ungaramense and indicate that they can be further developed through secretory cell culture techniques.